Infective Endocarditis: Systemic Inflammatory Response in Preoperative Heart Failure - Hanna B. Koltunova; Mikhailo Yu. Antomonov; Olena V. Rudenko (Український журнал серцево-судинної хірургії)
Surgical outcomes depend on several factors, including the choice of surgical procedure, surgical techniques and experience of medical center. Numerous nationwide population-based studies in Europe have shown an increase in the incidence of infective endocarditis (IE) by 4% per year. An important role in predicting the severity of the disease is played by the systemic inflammatory response, which is manifested by increased levels of inflammatory markers such as C-reactive protein and procalcitonin. The use of a complex of several inflammatory markers can potentially improve the analysis of the inflammatory response system and the assessment of treatment dynamics.